Edukasi dan Promosi Produk Halal (Kajian Literatur) - Hamka, Hamka; Siradjuddin, Siradjuddin; Efendi, Ahmad; Arifin, Asriadi (CV. Kalimasada Group, 2024)
The development of the world's sharia economy in the last few decades has not only made halal products an actual trend-send discourse as well as a policy reference in the local and even global sphere at this time. Indonesia is a country that has the largest Muslim population in the world, with statistics on the number of Indonesian Muslim population reaching 231.06 million people or representing 11.92% of the world's Muslim population. Estimated total spending on domestic halal products is considered to continue to grow to reach around USD 2.2 trillion. Based on the 2019/2020 State of Global Islamic Economy Report, Indonesia is now ranked 1st in the world as a consumer of halal food, 2nd in the world as a consumer of halal cosmetics, and 4th in the world as a consumer of halal medicines. To make Indonesia the mecca of world halal products, of course, one must be able to change consumptive habits to be productive. Therefore, to change these habits, several strategic actions are needed; namely promotion of halal products, education of halal products and no less important is the government improving the quality of halal product certification.